Positive electrode material, positive electrode sheet and secondary battery
By combining nickel, cobalt, manganese ternary material and lithium iron phosphate material in the positive electrode material to adjust its particle size distribution and specific surface area, the problem of being unable to achieve high energy density and high safety performance at the same time in the prior art is solved, and the battery is high Energy density and high safety synergistic effect.
Patent Information
- Application Number
- CN202210842756.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-18
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-07-18
AI Technical Summary
The existing positive electrode materials cannot have both high energy density and high safety performance. The energy density of ternary nickel-cobalt-manganese materials has high energy density but the circulation and safety performance needs to be improved. The safety performance of lithium iron phosphate materials has high safety performance but low voltage platform, so the energy density needs to be improved. promote.
The combination of nickel, cobalt, manganese ternary material and lithium iron phosphate material is used to satisfy specific relationships by adjusting the proportion of its particle size distribution and specific surface area to achieve a synergistic effect of high energy density and high safety. The specific method includes mixing nickel, cobalt, manganese ternary material and lithium iron phosphate material in the positive electrode material, and improving conductivity and stability through carbon coating to ensure that the particle size and specific surface area of the material are within a specific range.
The high energy density and high safety of the cathode material are achieved. By optimizing the material proportion and structure, the prepared battery cells have good energy density and safety performance, avoiding the shortage of a single material.
Smart Images

Figure BDA0003751751630000081 
Figure BDA0003751751630000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a positive electrode material, a positive electrode sheet and a secondary battery. Background Art
[0002] Lithium-ion battery positive electrode materials include lithium iron phosphate (LFP), lithium manganese oxide (LMO), lithium cobalt oxide (LCO), ternary nickel cobalt manganese (NCM), etc. The role of positive electrode materials is to provide a lithium source for lithium-ion batteries. The selection principle is that the electrode potential is high and can provide a high output voltage; the charge and discharge structure is stable and can ensure the cycle performance; the lithium ion chemical diffusion coefficient is high, the electron and ion conductivity is high, the resources are abundant, and the preparation cost is low. Usually, batteries prepared with a single positive electrode active material cannot take into account the advantages and disadvantages required by the market at the same time. For example, the ternary nickel cobalt manganese ternary material has a high energy density and a high discharge platform voltage (3.7V), but the cycle and safety performance need to be improved; lithium iron phosphate materials have high safety performance and a long cycle life, and the raw material resources are relatively abundant, but the voltage platform is low (3.2V), and the energy density needs to be improved. However, the existing materials cannot take into account both high energy density and high safety performance at the same time. Summary of the invention
[0003] One of the purposes of the present invention is to provide a positive electrode material to address the deficiencies of the prior art, thereby solving the problem that the positive electrode material cannot have both high energy density and high safety.
[0004] In order to achieve the above object, the present invention adopts the following technical solutions:
[0005] A positive electrode material includes a nickel-cobalt-manganese ternary material and a lithium iron phosphate material, wherein the nickel-cobalt-manganese ternary material and the lithium iron phosphate material satisfy the following relationship: 1≤(D 90LFP *X) / Z1+(D 90NCM *Y) / Z2=Q≤50;
[0006] Among them, D 90LFP It is the particle size corresponding to when the cumulative particle size distribution of lithium iron phosphate material reaches 90%;
[0007] Among them, D 90NCM is the particle size corresponding to when the cumulative particle size distribution of the nickel-cobalt-manganese ternary material reaches 90%; wherein Z1 is the specific surface area of the lithium iron phosphate material;
[0008] Wherein, Z2 is the specific surface area of the nickel-cobalt-manganese ternary material;
[0009] Wherein, X is the ratio of lithium iron phosphate material in the positive electrode material, and Y is the ratio of nickel-cobalt-manganese ternary material in the positive electrode material.
[0010] Preferably, the nickel-cobalt-manganese ternary material and the lithium iron phosphate material satisfy the following relationship: 16≤(D 90LFP *X) / Z1+(D 90NCM *Y) / Z2=Q≤45.
[0011] Preferably, the specific surface area Z1 of the lithium iron phosphate material is in the range of 8 to 15 m 2 / g, the mass percentage of carbon in the lithium iron phosphate material is 1-2%.
[0012] Preferably, the cumulative particle size distribution D of the lithium iron phosphate material is 10 ≥0.5μm, D 50 The value range is 1.5μm~2.1μm, D 90 ≤5.2μm, D 99 ≤9.5μm.
[0013] Preferably, the specific surface area Z2 of the nickel-cobalt-manganese ternary material is in the range of 0.5 to 1.1 m 2 / g, the pH value range is 10-12.
[0014] Preferably, the cumulative particle size distribution D of the nickel-cobalt-manganese ternary material is 10 ≥1μm, D 50 The value range is 2μm-6μm, D 90 The value range is 5μm-13μm, D 99 ≤18μm.
[0015] The second purpose of the present invention is to provide a positive electrode sheet with high energy density and high safety in view of the shortcomings of the prior art.
[0016] In order to achieve the above object, the present invention adopts the following technical solutions:
[0017] A positive electrode sheet comprises a positive electrode current collector and a positive electrode active coating arranged on at least one side of the positive electrode current collector, wherein the positive electrode active coating comprises the positive electrode material mentioned above.
[0018] The third object of the present invention is to provide a secondary battery with high energy density and high safety in view of the deficiencies of the prior art.
[0019] In order to achieve the above object, the present invention adopts the following technical solutions:
[0020] A secondary battery comprises a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and a shell, wherein the separator separates the positive electrode sheet from the negative electrode sheet, and the shell is used to encapsulate the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte, and the positive electrode sheet is the positive electrode sheet mentioned above.
[0021] Preferably, the isolation film is a polyethylene-based film, a polypropylene-based film, or a composite film of polyethylene and polypropylene.
[0022] Preferably, the electrolyte comprises a lithium salt, a solvent and an additive, the lithium salt is lithium hexafluorophosphate, the solvent is one or a mixture of ethylene carbonate, propylene carbonate or dimethyl carbonate, and the additive is one or a mixture of vinylene carbonate, propylene sulfite and fluoroethylene carbonate.
[0023] Compared with the prior art, the beneficial effect of the present invention is that the positive electrode material of the present invention combines the advantages of high energy density of nickel-cobalt-manganese ternary materials and the advantages of high safety of lithium iron phosphate materials, so that the two can play a synergistic role, maximize the excellent performance of the two materials, and make the prepared material have both good high energy density and high safety. DETAILED DESCRIPTION
[0024] The present invention will be described in further detail below in conjunction with specific implementation modes, but the implementation modes of the present invention are not limited thereto.
[0025] 1. A positive electrode material, comprising a nickel-cobalt-manganese ternary material and a lithium iron phosphate material, wherein the nickel-cobalt-manganese ternary material and the lithium iron phosphate material satisfy the following relationship:
[0026] 1≤(D 90LFP *X) / Z1+(D 90NCM *Y) / Z2=Q≤50;
[0027] Among them, D 90LFP It is the particle size corresponding to when the cumulative particle size distribution of lithium iron phosphate material reaches 90%;
[0028] Among them, D 90NCM It is the particle size corresponding to when the cumulative particle size distribution of the nickel-cobalt-manganese ternary material reaches 90%;
[0029] Wherein, Z1 is the specific surface area of lithium iron phosphate material;
[0030] Wherein, Z2 is the specific surface area of the nickel-cobalt-manganese ternary material;
[0031] Wherein, X is the ratio of lithium iron phosphate material in the positive electrode material, and Y is the ratio of nickel-cobalt-manganese ternary material in the positive electrode material.
[0032] The present invention takes the mixing ratio of nickel-cobalt-manganese ternary material and lithium iron phosphate material as the starting point, and verifies the mixed positive electrode of the two materials in different ratios, so that the positive electrode material has high energy density and high safety when applied to pole pieces and battery cells. The chemical formula of nickel-cobalt-manganese ternary material is Li a Ni x Co y Mnz O2, wherein x+y+z=1, 0.93<a<1.1, the chemical formula of lithium iron phosphate material is LiFePO4.
[0033] Preferably, the nickel-cobalt-manganese ternary material and the lithium iron phosphate material satisfy the following relationship: 16≤(D 90LFP *X) / Z1+(D 90NCM *Y) / Z2=Q≤45.
[0034] Nickel-cobalt-manganese ternary materials and lithium iron phosphate materials together form the positive electrode materials. The size of the material particle size is strongly correlated with the specific surface area of the material. The particle size of lithium iron phosphate material is relatively small and the specific surface area is large. The particle size of nickel-cobalt-manganese ternary materials is large and the specific surface area is relatively small. The size of the Q value can reflect the capacity and safety performance of the material to a certain extent. When the proportion of ternary materials is relatively large, that is, the Q value in the formula is greater than 45, the overall safety performance of the prepared battery cell is reduced. When the Q value is too low, the prepared battery cell has higher safety performance, but the corresponding energy density is relatively low. When 16≤Q value≤45 is satisfied, the positive electrode material takes into account both high energy density and high safety performance.
[0035] The present invention can use the above method to prepare the battery cell and make precise design, so that LFP and NCM can work together to achieve the best performance of the battery cell, while taking safety into consideration, and the corresponding energy density is also improved. 90 And the BET value is determined, D 90 / BET is a fixed value. Take this case as an example: D 90LFP =1.98, D 90NCM =5; Z1=10, Z2=1, we know D 90LFP / Z1=0.198,D 90NCM / Z2=5, where the total proportion of the two materials is 10, that is, X+Y=10 in the formula. It can be known that the Q value range is 1.98-50, and the corresponding ratio of the two materials is from 10:0 to 0:10. When the Q value is greater than 45, the safety performance of the battery cell will be reduced. When the Q value is ≤16, the energy density of the battery cell will be relatively low, and precise design can be carried out. The ratio of the two materials with both energy density and safety performance can be optimized. More importantly, as the example of preparing a 150wh / kg energy density battery cell given at the end of the article, precise design can be carried out.
[0036] The positive electrode material of the present invention combines the advantages of high energy density of nickel-cobalt-manganese ternary material and high safety of lithium iron phosphate material, so that the two can play a synergistic role, maximize the excellent performance of the two materials, and make the prepared material have both good high energy density and high safety.
[0037] Preferably, the specific surface area Z1 of the lithium iron phosphate material is in the range of 8 to 15 m 2 / g, the mass percentage of carbon in the lithium iron phosphate material is 1-2%. The specific surface area Z1 of the lithium iron phosphate material ranges from 8 to 15 m 2 / g, 8~12m 2 / g, 10~12m 2 / g, 10~11m 2 / g, specifically, the specific surface area Z1 of the lithium iron phosphate material is 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g. The mass percentage of carbon in lithium iron phosphate materials is 1-2%, 1.2%-1.8%, 1.3%-1.6%, 1.5%-1.6%. Specifically, the mass percentage of carbon in lithium iron phosphate materials is 1%, 1.2%, 1.5%, 1.6%, 1.8%, and 2%. The carbon in lithium iron phosphate materials covers the surface of lithium iron phosphate particles by means of coating. If the specific surface area Z1 is too large, it means that the particle size is small, and more auxiliary materials such as adhesives will be required when used, which is not conducive to the performance of the material. If it is too small, it means that the particle size is large, which will increase the transmission channels of electrons and lithium ions, and is not conducive to the performance of the material. Carbon coating will increase the conductivity between LFP particles, reduce the capacity attenuation under high rate conditions, and improve the rate characteristics and low temperature performance. Too little will not achieve the above effects. Too much will waste the proportion of the main material and reduce the overall capacity of the material.
[0038] Preferably, the cumulative particle size distribution D of the lithium iron phosphate material is 10 ≥0.5μm, D 50 The value range is 1.5μm~2.1μm, D 90 ≤5.2μm, D 99 ≤9.5μm. Cumulative particle size distribution D of lithium iron phosphate material 10 0.5μm, 0.8μm, 1.2μm, 1.5μm. D 50 The value range is 1.5μm~2.1μm, 1.6μm~2.0μm, 1.8μm~1.9μm. Preferably, D 50The values are 1.5μm, 1.6μm, 1.8μm, 1.9μm, 1.9μm, 2μm, and 2.1μm. If the specific surface area Z1 of lithium iron phosphate material is too large, it means that the particle size is small, and more auxiliary materials such as adhesives will be required when used, which is not conducive to the performance of the material. If it is too small, it means that the particle size is large, which will increase the transmission channels of electrons and lithium ions, which is not conducive to the performance of the material. Carbon coating will increase the conductivity between LFP particles, reduce the capacity attenuation under high rate conditions, and improve the rate characteristics and low temperature performance. Too little will not achieve the above effects. Too much will waste the proportion of the main material and reduce the overall capacity of the material. Therefore, through the above-mentioned limitation on the particle size, the particle size is within a certain range, which is conducive to taking into account conductivity, capacity, and rate performance.
[0039] Preferably, the specific surface area Z2 of the nickel-cobalt-manganese ternary material is in the range of 0.5 to 1.1 m 2 / g, the pH value range is between 10 and 12. The specific surface area Z2 of the nickel-cobalt-manganese ternary material ranges from 0.5 to 1.1 m 2 / g, 0.6~1.1m 2 / g, 0.8~1.1m 2 / g, 0.8~1.0m 2 / g, 0.8~0.9m 2 / g, specifically, the specific surface area Z2 of the nickel-cobalt-manganese ternary material is 0.5m 2 / g, 0.6m 2 / g, 0.8m 2 / g, 1.1m 2 / g. The pH values of nickel-cobalt-manganese ternary materials are 10, 11, and 12. If the pH value range of nickel-cobalt-manganese ternary materials is too small, it will easily affect the processing performance and deteriorate the processing performance. If the pH value is too large, the material will be too alkaline, which may cause the slurry to gel during stirring, which is not conducive to the mixing of materials. If the specific surface area Z2 of the nickel-cobalt-manganese ternary material is too large, it means that the particle size is small, and more auxiliary materials such as adhesives will be required during use, which is not conducive to the performance of the material. If it is too small, it means that the particle size is large, which will increase the transmission channels of electrons and lithium ions, and is not conducive to the performance of the material. Carbon coating will increase the conductivity between nickel-cobalt-manganese ternary particles, reduce the capacity attenuation under high rate conditions, and improve the rate characteristics and low temperature performance. Too little will not achieve the above effects. Too much will waste the proportion of the main material and reduce the overall capacity of the material. Therefore, through the above-mentioned limitation on the particle size, the particle size is within a certain range, which is conducive to taking into account conductivity, capacity, and rate performance.
[0040] Preferably, the cumulative particle size distribution D of the nickel-cobalt-manganese ternary material is 10 ≥1μm, D 50 The value range of D is 2μm~6μm,90 The value range of D is 5μm~13μm, 99 ≤18μm. Cumulative particle size distribution D of nickel-cobalt-manganese ternary material 10 1μm, 3μm, 5μm, 7μm, 9μm. D 50 The value range of D is 2μm~6μm, 3μm~6μm, 4μm~6μm, 4μm~5μm. Specifically, D 50 The value range of D is 2μm, 3μm, 4μm, 5μm, 5.5μm, and 6μm. 90 The value range of D is 5μm~13μm, 6μm~13μm, 8μm~13μm, 9μm~13μm, 8μm~10μm. 90 The values are 5μm, 7μm, 9μm, 10μm, 11μm, 12μm, and 13μm. These are the conventional physical properties of NCM materials. If they are too large or too small, they are not in line with the process flow and performance we are currently using.
[0041] 2. A positive electrode sheet with high energy density and high safety.
[0042] A positive electrode sheet comprises a positive electrode current collector and a positive electrode active coating arranged on at least one side of the positive electrode current collector, wherein the positive electrode active coating comprises the positive electrode material mentioned above.
[0043] Preferably, both sides of the positive electrode sheet are coated with a positive electrode active coating, and the thickness of the positive electrode active coating is 10-16 μm. The positive electrode current collector is copper foil.
[0044] 3. A secondary battery with high energy density and high safety.
[0045] A secondary battery comprises a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and a shell, wherein the separator separates the positive electrode sheet from the negative electrode sheet, and the shell is used to encapsulate the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte, and the positive electrode sheet is the positive electrode sheet mentioned above.
[0046] Preferably, the isolation film is a polyethylene-based film, a polypropylene-based film, or a composite film of polyethylene and polypropylene. Preferably, the surface of the isolation film can be coated with ceramic or adhesive.
[0047] Preferably, the electrolyte comprises a lithium salt, a solvent and an additive. Preferably, the weight ratio of the lithium salt, the solvent and the additive is 40-60:80-110:2-8, and more preferably, the weight ratio of the lithium salt, the solvent and the additive is 50:85:6.
[0048] Preferably, the lithium salt is lithium hexafluorophosphate, the solvent is one or a mixture of ethylene carbonate, propylene carbonate or dimethyl carbonate, and the additive is one or a mixture of vinylene carbonate, propylene sulfite and fluoroethylene carbonate.
[0049] Group AG: Preparation of positive electrode sheets with different active material ratios: the positive electrode active material is lithium iron phosphate + lithium nickel cobalt manganese oxide, and the positive electrode active material is LFP + NCM: CNT: SP: PVDF mixed at a mass ratio of 97%: 0.5%: 1%: 1.5%; mixed and stirred in the same stirring tank, and coated on copper foil; when LFP: NCM = 10: 0, the applicable compaction density range of the electrode sheet is 2.4-2.7g / cm 3 , the pole piece is marked as P1; when LFP:NCM=9:1, the applicable compaction density range of the pole piece is 2.5-2.8g / cm 3 , the pole piece is marked as P2; when LFP:NCM=7:3, the applicable compaction density range of the pole piece is 2.6-3.1g / cm 3 , the pole piece is marked as P3; when LFP:NCM=5:5, the applicable compaction density range of the pole piece is 3.0-3.25g / cm 3 , the pole piece is marked as P4; when LFP:NCM=2:8, the applicable compaction density range of the pole piece is 3.1-3.6g / cm 3 , the pole piece is marked as P5; when LFP:NCM=1:9, the applicable compaction density range of the pole piece is 3.2-3.7g / cm 3 , the pole piece is marked as P6; when LFP:NCM=0:10, the applicable compaction density range of the pole piece is 2.2-3.9g / cm 3 , marking the electrode as P7. In the positive electrode materials of P1-P7 above, D 90LFP =1.98, Z1=10, D 90NCM =5, Z2=1.
[0050] The negative electrode sheet is prepared. The negative electrode active material is artificial graphite. The negative electrode formula is C:SP:CMC:SBR=96%:1%:1.5%:1.5%; it is mixed and stirred in a mixing tank and coated on both sides of the aluminum foil. The compaction density is 1.4-1.7g / cm 3 , mark the pole piece as N.
[0051] Preparation of electrolyte:
[0052] Lithium hexafluorophosphate (LiPF6) is dissolved in a mixed solvent consisting of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) (the mass ratio of the three is 1:2:1) to obtain an electrolyte with a concentration of 1 mol / L.
[0053] Preparation of battery cells: Use P1-P7 positive electrode sheets and N negative electrode sheets respectively, wind or stack the positive electrode sheets, negative electrode sheets, and polypropylene separators, and obtain complete battery cells through baking, liquid injection, formation, and capacity separation. The battery cells prepared by stacking the positive and negative electrode sheets of P1-P7 are marked as A, B, C, D, E, F, and G, a total of seven groups of battery cells. The prepared battery cells are tested with a charge and discharge rate of 1C and a charge and discharge voltage range of 2.5-4.35V.
[0054] Needle puncture safety performance test: After the battery is fully charged to 4.2V in a constant current and constant voltage mode, a high temperature resistant steel needle of Φ3mm to Φ8mm is used to penetrate the battery plate perpendicularly at a speed of 10mm / s to 40mm / s. The steel needle stays in the battery for 1 hour. Definition of the results of the safety performance test: "no smoke, no fire, no explosion" is "passed"; "smoke, sparks, no explosion" is "substandard"; "smoke, fire" is "bad", and "fire and explosion" is "failed".
[0055] Discharge gram capacity test: Place the button cell to be tested in a 25±3℃ environment for 30 minutes, charge at a constant current rate of 0.1C to a voltage of 4.4V (rated voltage), then charge at a constant voltage to a current of 0.025C, and then discharge at rates of 0.1C, 0.2C, 0.5C, 1C and 2C to 3V (cut-off voltage), and record the discharge gram capacity at different discharge rates. Discharge gram capacity = discharge capacity / weight of positive electrode active material.
[0056] Energy density test: The energy of the battery when discharged from 100% SOC to the cut-off voltage is divided by the battery weight.
[0057] Table 1
[0058]
[0059]
[0060] As shown in Table 1 above, the gram capacity of the prepared battery cell increases with the increase in the mass ratio of the nickel cobalt manganese oxide material. When the addition amount reaches 30% or more, the discharge voltage platform of the battery cell and the increase in the battery cell capacity are more obvious, and the energy density of the prepared battery cell is also greatly increased; after the battery cell is fully charged with 1C and then subjected to a needle puncture safety test, it can be seen that the F / G group battery cells smoke and catch fire, and the corresponding addition amounts of the ternary nickel cobalt manganese oxide material are 90% and 100% respectively. Therefore, when the addition amount is increased to 90% or more, although the energy density is higher, the safety performance of the battery cell will be sacrificed to a certain extent. Therefore, considering comprehensively, when 16≤Q value<45 should be satisfied, the prepared secondary battery is better with good high energy density and high safety performance.
[0061] Different sized cells made of the same material will have different energy densities. The addition of ternary materials will increase the energy density of the cell to a certain extent. According to the example, when the energy density is required to be 150Wh / kg, the corresponding Q value range is 16<Q<25.99. At this time, the ratio of LFP:NCM is limited to 7:3 to 5:5. At this time, it can be assumed that the Q value is linearly related to the energy density. At this time, the Q value is 18.16. By calculation, at this time, x=6.63, y=3.37, and the ratio of LFP:NCM is 6.63:3.37.
[0062] The positive electrode material of the present invention imposes corresponding restrictions on the nickel-cobalt-manganese ternary material and the lithium iron phosphate material, so that the specific surface area, cumulative particle size distribution and ratio of the two materials are within a certain range, thereby making the prepared positive electrode material have both better energy density and better safety performance.
[0063] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A positive electrode material, characterized in that: It includes a nickel-cobalt-manganese ternary material and a lithium iron phosphate material, and the nickel-cobalt-manganese ternary material and the lithium iron phosphate material satisfy the following relationship: 16.39≤(D 90LFP *X) / Z1+(D 90NCM *Y) / Z2=Q≤25.99; Among them, D 90LFP The particle size corresponding to the cumulative particle size distribution of the lithium iron phosphate material reaches 90%; the cumulative particle size distribution D50 of the lithium iron phosphate material has a value range of 1.5 μm to 2.1 μm, and D90 ≤ 5.2 μm; Among them, D 90NCM It is the particle size corresponding to when the cumulative particle size distribution of the nickel-cobalt-manganese ternary material reaches 90%; the value range of the cumulative particle size distribution D90 of the nickel-cobalt-manganese ternary material is 5μm to 13μm; Wherein, Z1 is the specific surface area of the lithium iron phosphate material; the specific surface area Z1 of the lithium iron phosphate material ranges from 8 to 15 m 2 / g; Wherein, Z2 is the specific surface area of the nickel-cobalt-manganese ternary material; the specific surface area Z2 of the nickel-cobalt-manganese ternary material ranges from 0.5 to 1.1 m 2 / g; Among them, X is the proportion of lithium iron phosphate material in the positive electrode material, Y is the proportion of nickel cobalt manganese ternary material in the positive electrode material, X+Y=10, and X:Y is 7:3~5:
5.
2. The positive electrode material according to claim 1, characterized in that The mass percentage of carbon in lithium iron phosphate material is 1~2%.
3. The positive electrode material according to claim 1 or 2, characterized in that The cumulative particle size distribution D of the lithium iron phosphate material 10 ≥0.5μm.
4. The positive electrode material according to claim 1, characterized in that The pH value of the nickel-cobalt-manganese ternary material ranges from 10 to 12.
5. The positive electrode material according to claim 1 or 4, characterized in that: The cumulative particle size distribution D of the nickel-cobalt-manganese ternary material 10 ≥1μm, D 50 The value range is 2μm-6μm, D 99 ≤18μm.
6. A positive electrode sheet, characterized in that: The invention comprises a positive electrode current collector and a positive electrode active coating arranged on at least one side of the positive electrode current collector, wherein the positive electrode active coating comprises the positive electrode material according to any one of claims 1 to 5.
7. A secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and a shell, wherein the separator separates the positive electrode sheet and the negative electrode sheet, and the shell is used to encapsulate the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte, and the positive electrode sheet is the positive electrode sheet according to claim 6.
8. The secondary battery according to claim 7, characterized in that: The isolation film is a polyethylene-based film, a polypropylene-based film, or a composite film of polyethylene and polypropylene.
9. The secondary battery according to claim 7, characterized in that: The electrolyte includes a lithium salt, a solvent and an additive, wherein the lithium salt is lithium hexafluorophosphate, the solvent is one or a mixture of ethylene carbonate, propylene carbonate or dimethyl carbonate, and the additive is one or a mixture of vinylene carbonate, propylene sulfite and fluoroethylene carbonate.